2016
DOI: 10.1155/2016/3410213
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Safety of Shihogyejitang for Drug Resistant Childhood Epilepsy

Abstract: Objective. Herbal medicine has been widely used to treat drug resistant epilepsy. Shihogyejitang (SGT) has been commonly used to treat epilepsy. We investigated the effect and safety of SGT in children with drug resistant epilepsy. Design. We reviewed medical records of 54 patients with epilepsy, who failed to respond to at least two antiepileptic drugs and have been treated with SGT between April 2006 and June 2014 at the Department of Pediatric Neurology, I-Tomato Hospital, Korea. Effect was measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
1
1
Order By: Relevance
“…Wray et al 18 reported that children who did not experience seizure tended to use CAM, which contrasts with our results showing a higher proportion of children with seizure in the TKM-use group than in the no-TKM-use group. The reasons for this difference could not be determined in the present study, but previous studies have revealed that children who experience seizure use TKM relatively frequently in South Korea 9 and that resistant childhood epilepsy is often treated with herbal medication 25 . Children who had other health problems used TKM more often than children without other health issues.…”
Section: Discussioncontrasting
confidence: 56%
“…Wray et al 18 reported that children who did not experience seizure tended to use CAM, which contrasts with our results showing a higher proportion of children with seizure in the TKM-use group than in the no-TKM-use group. The reasons for this difference could not be determined in the present study, but previous studies have revealed that children who experience seizure use TKM relatively frequently in South Korea 9 and that resistant childhood epilepsy is often treated with herbal medication 25 . Children who had other health problems used TKM more often than children without other health issues.…”
Section: Discussioncontrasting
confidence: 56%
“…These herbs were reported to be effective in the treatment of epilepsy, all without side effects. Shihogyejitang (SGT), a herbal medication, was studied in Korea, in which a retrospective study of pediatric patients with drug-resistant epilepsy using SGT were analyzed [ 42 ]. Over 44% of the patients showed a greater than 50% reduction in seizures, with 24% being seizure free.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the onset of FS usually occur suddenly when the family members of children are unprepared. The family members of children are more stressed, often accompanied by negative emotions such as irritability and anxiety ( Yilmaz et al, 2008 ; Lee et al, 2016 ; Mosili et al, 2020 ; Wubetu et al, 2020 ; Bing et al, 2022 ), resulting in higher expectations for quality of nursing and the need for caring care, and increased difficulty for the nursing staff. Studies ( Lee et al, 2016 ) have pointed out that taking targeted nursing intervention after fully understanding the nursing needs of children’s families can effectively correct the bad psychological behaviors of children’s families, which is extremely important for promoting children’s recovery and building a harmonious doctor-patient and nurse–patient relationship ( Sakai et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%